Rob Thelen letter to Thomas Kent regarding spring report, spring 1995 - Thelen, Robet al (1995)
Undated letter from Rob Thelen to Thomas Kent. Thelen sends Kent his spring report. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1995. Epson - sheet feed/flatbed